Writing Double: Politics and The African Narrative of French Expression - John D. Erickson (Studies in 20th & 21st Century Literature, 1991)
This essay studies two African narratives of French expression (Le Temps de Tamango of Boubacar Diop and L'Enfant de sable of Tahar ben Jelloun) to see how they create a discourse of difference that challenges and deconstructs the conventions of the discursive system of French, its signifying practices, and its ideological underpinnings. The tactics of these narratives, which mark them as post-colonial in a strict sense (as opposed to neo-colonial), are productive of a radical other-meaning, a new meaning that "speaks" to the concerns of and problems confronting the non-Western writer.
Keywords: African narratives; French expression; French; Le Temps de Tamango; Boubacar Diop; L' Enfant de sable; Tahar ben Jelloun; discourse of difference; discourse; difference; deconstructs; discursive system of French; signifying; ideological; post-colonial; neo-colonial; speaks; non-Western writer